Challenges in implementing English-only instruction: Insights from EFL student teachers in Taiwan - Jackie Chang (Studies in English Language and Education)
English-only instruction is promoted intensely by the Taiwanese government as an effective method to enhance students’ English language skills in primary schools. Determining how to effectively employ English-only instruction is a major concern for many English educators and authorities in Taiwan. This study explored the challenges encountered by English as a Foreign Language (EFL) student teachers in their English language proficiency while providing English-only instruction in an English language teaching practicum at a Taiwanese elementary school. A qualitative research design was employed in this study. The participants of this study consisted of 11 EFL student teachers. Lesson plans, class observations, and reflective journal entries were the sources of the research data in this study. A thematic analysis was employed to analyze the data of this study. The results indicate that EFL student teachers’ English language proficiency gave them challenges while employing English-only instruction due to inappropriate and inadequate English usage, poor presentation, and infallible native speaker models. Moreover, there is no clear link between EFL student teachers’ English proficiency and their teaching effectiveness. The results also imply that the challenges encountered by EFL student teachers regarding their English language proficiency in employing English-only instruction are related to micro (classroom) and macro (Taiwanese society) relations. The results further provide insights for those involved in designing English-only instruction training programs to be more critically concerned about designing effective pre-service or in-service training programs for EFL teachers.